The Ligation in echelon of hemorrhoids.: Experience of 100 patients operated upon. Results. - Estefan, Alberto; Beguiristain, Alberto; Praderi, José; Grezzi, Roberto; Esperón, Ruben (Cirugía del Uruguay, 1985)
Analysis of a series of 100 patients with hemorrhoids grade 111, tr-eated by means of the ligatlon in echelon. Excelléht results have been obtained by this procedure in the short and the long term.